Human Capital, Economic Growth and Environmental Quality with Special Emphasis on Public Education Expenditures: An Application of DSGE Models - Yahya Mohaghegh; hashem zare; Mehrzad Ebrahimi (پژوهشهای اقتصادی)
Aim and Introduction The world has suffered severe environmental degradation in the last two decades. The effects of ecological deviations and environmental destruction are alarming and cause concern for stakeholders and environmentalists. These problems have led to environmental disasters such as extreme weather changes and rising sea levels. For this reason, countries are trying to address environmental crises and economic growth at the same time. Basically, it is believed that the destruction of ecosystems in many countries is the result of human actions, including rapid industrialization, population growth, expansion of economic activities, urbanization, and widespread consumption of fossil fuels. Undoubtedly, one of the main factors of climate change and environmental degradation is the emission of carbon dioxide (CO2) caused by economic activities. The relationship between carbon dioxide emissions and economic growth has attracted the attention of researchers and policymakers to reduce carbon dioxide emissions without affecting economic growth. Achieving this goal may be difficult, but studies have included various factors in the growth-carbon dioxide relationship, such as different energy sources, technological innovations, population, financial development, urbanization, and trade openness. In addition to the factors mentioned above, there is a need to assess other relevant factors such as human capital for effective policy development. Despite the extensive role of human capital in promoting energy efficiency and economic growth, by skilled workers in the production process and the preference of educated households to use home appliances with high energy efficiency, few researchers have included this factor in the existing literature. Education is considered as one of the most important human capital investments and plays a vital role in the process of economic growth. Education, at the micro level, affects the future income flow of people, and at the macro level, it is thought that a workforce with better education increases the stock of human capital in the economy. Increased human capital in turn can have positive externalities, such as lower crime or improved health outcomes, which are socially desirable and likely to have positive effects on productivity. In fact, it is the existence of such positive externalities that provides economic justification for governments to support education. It is believed that public spending on education and health will lead to improvement of human capital, reduction of poverty, economic growth and development, and reduction of pollution. Theoretical studies emphasize different mechanisms through which education affects economic growth. (1) Education increases the human capital of the labor force, thereby increasing labor productivity and shifting growth toward a higher equilibrium level of output. (2) In endogenous growth theories, education increases the economy's capacity to innovate new technologies, products, and processes, thereby promoting growth. In the environmental field, improving human capital can reduce the use of fossil fuel in the production process. The motive of this research is to understand the effect of public education expenditure shocks on economic growth and environmental quality in Iran. Methodology To achieve the goal of the research, a dynamic stochastic general equilibrium (DSGE) model and Bayesian approach have been used. In this regard, observable variables, gross domestic product, private consumption, investment, government expenditure and the gross growth rate of money have been used in the period of 2004 to 2021. Findings The results indicate that an increase in public education expenses by one standard deviation increases the marginal efficiency of private education expenses. Because private and public education expenses complement each other and entered the model in the form of a Cobb-Douglas function. Therefore, education hours, investment in education and subsequently, human capital increased. The increase in human capital led to an increase in production, economic growth and a decrease in inflation. The decrease in inflation led to an increase in the real wages of the workforce and finally the desire of the household to increase the supply of labor. Consumption increased in response to an increase in real wages. Also, the behavior of investment is very similar to the behavior of consumption and production, but its changes are more intense than other expenses. Therefore, it can be said that the shock of public education expenses has affected the performance of the economy like an expansionary impulse and has improved the economic conditions. In the environmental sector, with the increase in human capital, economic growth has been improved and this has led to an increase in air pollution and a decrease in environmental quality. Discussion and Conclusion In justifying these results, we can point to the weak institutional quality in Iran, that despite the huge amount of human capital investment, there is no necessary effectiveness in the environmental sector, and this is a confirmation that Iran is in the early stages of economic development. As a policy recommendation, in addition to paying attention to education and its role in the development of human capital as a long-term investment, improving the quality of institutions should be considered